Impact of land composition and configuration on the functional trait assembly of forest communities in southern Ontario. Issue 3 (18th March 2019) - Miedema, Liane J.; Capmourteres, Virginia; Anand, Madhur
Abstract: The conversion of natural lands to agricultural and urban areas is the leading cause of biodiversity loss worldwide, and an understanding of functional trait assembly pattern can help to mitigate the ecological implications of this loss. We use plant functional traits—characteristics of the plant that determine how they react to and interact with the surrounding ecosystem—to assess the impacts of landscape composition and configuration on plant community assembly patterns in the multiple‐use Credit River watershed, Southern Ontario. We examine functional patterns in metacommunities to uncover how eight landscape variables (including both agricultural and urban uses) affect community assembly patterns and which traits explain these assembly patterns. We find that landscape variables result in significant trait‐divergence assembly patterns at two spatial scales (1 and 10 km), which means that these forest communities are more functionally diverse than would be expected by chance. Additionally, the optimal functional traits that maximize divergence in the community are dependent on landscape variables. We discuss three mechanisms—limiting similarity, niche availability, disturbance—that might be responsible for the trait divergence observed. First, we propose that limiting similarity could lead to trait divergence through niche differentiation and thus coexistence of more traits. Second, we argue that mosaic landscapes provide multiple and diverse habitats in which more species, likely with differing functional traits, can occur. Finally, we discuss how disturbances could prevent dominant species from competitively excluding others, thus favoring coexistence of functional traits.